Marula oil nanoemulsion improves motor function in experimental parkinsonism via mitigation of inflammation and oxidative stress - Alshaman, Reem; Qushawy, Mona; Mokhtar, Hatem I.; Ameen, Angie M.; El-Sayed, Rehab M.; Alamri, Eman Saad; Elabbasy, Lamiaa M.; Helaly, Ahmed M. N.; Elkhatib, Walid F.; Alyahya, Eidah M.; Zaitone, Sawsan A. (Frontiers in Pharmacology, 2023)
Parkinson's disease (PD) is a neurologic condition exhibiting motor dysfunction that affects old people. Marula oil (M-Oil) has been used longley in cosmetics and curing skin disorders. M-Oil is particularly stable due to its high concentration of monounsaturated fatty acids and natural antioxidants. The current study formulated M-Oil in an o/w nanoemulsion (M-NE) preparations and tested its anti-inflammatory and antioxidant actions against experimental parkinsonism. Four experimental groups of male albino mice were used and assigned as vehicle, PD, PD + M-Oil and PD + M-NE. Locomotor function was evaluated using the open field test and the cylinder test.Striatal samples were used to measure inflammatory and oxidative stress markers. The results indicated poor motor performance of the mice in PD control group then, improvements were recorded after treatment with crude M-Oil or M-NE. In addition, we found high expression and protein of inflammatory markers and malondialdehyde levels in PD group which were downregulated by using doses of crude M-Oil or M-NE. Hence, formulating M-Oil in form of M-NE enhanced its physical characters. This finding was supported by enhanced biological activity of M-NE as anti-inflammatory and antioxidant agent that resulted in downregulation of the inflammatory burden and alleviation of locomotor dysfunction in experimental PD in mice.